Reliability of Transcallosal Inhibition in Healthy Adults - Fleming, Melanie K.; Newham, Di J. (Frontiers in Human Neuroscience, 2017)
Transcallosal inhibition (TCI), assessed using transcranial magnetic stimulation (TMS), can provide insight into the neurophysiology of aging and of neurological disorders such as stroke. However, the reliability of TCI using the ipsilateral silent period (iSP) has not been formally assessed, despite its use in longitudinal studies. This study aimed to determine the reliability of iSP onset latency, duration and depth in healthy young and older adults. A sample of 18 younger (mean age 27.7 years, range 1 9 – 42) and 13 older healthy adults (mean age 68.1 years, range 58 – 79) attended four sessions whereby the iSP was measured from the first dorsal interosseous (FDI) muscle of each hand. 20 single pulse stimuli were delivered to each primary motor cortex at 80 % maximum stimulator output while the participant maintained an isometric contraction of the ipsilateral FDI. The average onset latency, duration of the iSP, and depth of inhibition relative to baseline electromyography (EMG) activity was calculated for each hand in each session. Intraclass correlation coefficients (ICCs) were calculated for all four sessions, or the first two sessions only. For iSP onset latency the reliability ranged from poor to good. For iSP duration there was moderate to good reliability (ICC > 0.6). Depth of inhibition demonstrated variation in reproducibility depending on which hand was assessed and whether two or four sessions were compared. Bland and Altman analyses showed wide limits of agreement between the first two sessions, particularly for iSP depth. However, there was no systematic pattern to the variability. These results indicate that although iSP duration is reliable in healthy adults, changes in longitudinal studies should be interpreted with caution, particularly for iSP depth. Future studies are needed to determine reliability in clinical populations.